Tearing the envelope: from tunnel to tower industrial typology - Saville, Ivor (School of Architecture, Planning and Geomatics, 2018)
The following dissertation responds to the industrially significant Maitland/Salt River area of Cape Town, Western Cape. Over time, industrial stock has resulted in ruin due to the unpredictable reality of industry, and competing for business globally. Exploring the possibility of the area to be developed as an industrially significant urban quarter seeks to revive investment in existing industry. The revival requires a shift in business and architectural model that encourages adaptability through rethinking the scale of production/manufacture and tenancy. Current single tenancy models operate with a ground floor sprawling line of production, prioritising the machine in a controlled environment. This requires a rigid form of enclosure, defined in this research as the envelope. Research has suggested that the scale of manufacture should decrease, providing the opportunity of a hybrid, mixed-use industrial typology. The intention is to vacate space on an industrial site to cater for an interface with the public. Visual and physical connections with the local urban condition will allow the factory to contribute to the revived intention of industrial urbanism in the area. The Jensen Belts leather factory will be used as this study's existing building to be adapted. Currently the circulation of production and goods is isolated from the circulation of the public which results in the factory creating a black box surrounded by negative space in the city. Prioritising the circulation of goods creates an environment that is not conducive to human comfort - highlighting the sheltering priority of the existing factory, to house goods and not people. Focusing specifically on leather production, rethinking the connection between the circulation of goods and people establishes the industrially significant presence through the theatre of production in the city. The proposal of a future factory lies in rethinking the production line model to limit the amount of space it occupies - offering loose space for multiple tenancy. Multiple tenancy describes the hybrid typology proposed to cater for the varying needs of the Maitland context. These needs involve employment and upskilling, which are catered for in a responding Community Workshop Model. The first architectural investigation seeks to 'tear' the tightly sealed factory building envelope once the controlled production line model shifts. The second architectural enquiry is in the design of an adaptable vertical tower that houses the possible phases of needs in the typical industrial building life cycle. The tower is seen to anchor a hybrid community workshop program. The existing building and site constraints, tunnelling the production process, provides a platform to propose a strategy for a new, bold structure that shifts the program to prioritise the comfort of the user. In response to the existing controlled production line model that excludes the public, the new model seeks to expose the program to connect to the site's range of urban networks positively. The area offers a wealth of key infrastructural networks (M5 highway underpass, railway, Black River, West end of Voortrekker Road) that have resulted in spatial boundaries. With the interest of 'tearing' the factory building envelope for integration, the urban investigation seeks to establish ways of inhabiting and crossing these architectural and urban boundaries to foster connection.